Acute hyperthermia and hypoxia tolerance of two improved strains of nile tilapia (Oreochromis niloticus) - Duodu, C. P.; Obirikorang, K.A; Appiah‑Kubi, R.; et al. (Springer, 2023)
Abstract Tilapia production in Ghana has been hit with episodes of stress and pathogen-induced mass fsh kills which have anecdotally been linked to the culture of illegally imported Genetically Improved Farmed Tilapia (GIFT) strains of Nile tilapia, Oreochromis niloticus. This study was thus set up to comprehensively assess the stress tolerance of the GIFT strain and a native strain of Nile tilapia (the Akosombo strain) following exposures to hyperthermic and hypoxic stressors. In a series of experiments, oxygen consumption (MO2), aquatic surface respiration (ASR), thermal limits and hypoxia tolerance were assessed. The efects of these stressors on haematological parameters were also assessed. The GIFT strain was less tolerant of hypoxia and performed ASR at higher O2 levels than the Akosombo strain. Under progressive hypoxia, the GIFT strain exhibited higher gill ventilations frequencies (fV) than the Akosombo strain. The thermal tolerance trial indicated that the Akosombo strain of O. niloticus has higher thermotolerance than the GIFT strain and this was refective in the higher LT50 (45.1℃) and LTmax (48℃), compared to LT50 and LTmax of 41.5℃ and 46℃ respectively. These results imply that it is crucial to consider how the GIFT strain performs under various envi‑ ronmental conditions and changes during culture. Particularly, raising the GIFT strain of Nile tilapia in earthen ponds rich in phytoplankton and subject to protracted episodes of extreme hypoxia may have a detrimental physiological impact on its growth and welfare.
Research Article
Keywords: Aquaculture; Aquatic hypoxia; Environmental stressors; Oxygen; Temperature